Economics Today - Economics Tomorrow - Ratajczak, Marek (Studia Oeconomica Posnaniensia, 2017)
We can observe a very interesting and animated discussion on the condition of economics from the very beginning of the last world crisis. Th e paper as an element of these discussions has two goals. Th e fi rst goal is to present the main elements of methodological debate on economics. Th e second objective is to present a vision of changes that are necessary to make economics more appropriable to modern social demands. On one the hand the author does not accept the idea of a crisis of economics in the sense of total failure especially of mainstream economics. On the other hand the author believes that economics is in crisis in the sense of Th omas Kuhn’s idea of the scientifi c revolution.